The Formulation of the Idea of Forgiveness in Indonesian Criminal Law Policy (A Study Based on Restorative Justice & Pancasila Values) - Ira Alia Maerani; Siti Rodhiyah Dwi Istinah (Jurnal Daulat Hukum, 2022)
This study aims to analyze the idea (value) of forgiveness as the noble value of the Indonesian nation into a national legal product. History records that in various literatures, when various national problems were recorded, it was revealed that the idea, nature, value of forgiveness became one of the key values for the success of the Indonesian nation in reducing various kinds of criminal and social conflicts problems in society. So that the expected restorative justice for those who are litigated can be achieved. Indeed, the Indonesian people are familiar with this non-penal problem model through deliberation as a step in implementing the values of Pancasila. However, considering that national legal products still use legal products inherited from the colonialists, there are differences in the values adopted by the colonial nation and the noble values of the Indonesian nation. The subject studied in this study is to determine the provisions of the idea of forgiveness in the current positive criminal law policy (Ius Constitutum; future criminal law policy (ius constituendum) and efforts to reconstruct national criminal law policies by prioritizing the idea of Forgiveness as the noble values of the Indonesian nation is based on restorative justice and the values of Pancasila. The research method used in this study is a normative juridical approach. Types and sources of data used are secondary data with data collection methods are through document studies and literature studies. The expected result of this research is the internalization of the value (idea) of forgiveness in national legal products; the accommodation of restorative justice as a solution to various legal and social problems in society; there is the principle of legality and legal certainty in applying restorative justice by law enforcement; and growing confidence to put forward the values of Pancasila in solving legal conflicts and social problems in society.